1986
DOI: 10.2337/diacare.9.3.267
|View full text |Cite
|
Sign up to set email alerts
|

Use of Liquid Crystal Thermography in the Evaluation of the Diabetic Foot

Abstract: Liquid crystal thermography (LCT) was used to determine temperature variations on the plantar surface of feet. The purpose was to identify thermal emission patterns associated with diabetic foot ulcers. Three population groups were screened: group I, 16 nondiabetic controls; group II, 21 diabetic patients with no history of pedal ulcers; and group III, 28 diabetic patients with active pedal ulceration or history of foot ulcerations. The results demonstrate a generalized increase in plantar foot temperature in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 0 publications
1
43
0
3
Order By: Relevance
“…Inflammation is one of the earliest signs of tissue injury and ulceration (5)(6)(7)(8). However, the clinical signs of inflammation are usually too subtle to be detected by patients or even by trained health care providers (9).…”
mentioning
confidence: 99%
“…Inflammation is one of the earliest signs of tissue injury and ulceration (5)(6)(7)(8). However, the clinical signs of inflammation are usually too subtle to be detected by patients or even by trained health care providers (9).…”
mentioning
confidence: 99%
“…Using LC thermography, Chan et al (Chan et al, 1991) designated temperature distribution in normal subjects as a "symmetrical butterfly pattern" in which the medial arch showed the highest temperature as reported by Sun et al (Sun et al, 2005;Sun et al, 2006). However, Stess et al (Stess et al, 1986) indicated that such a typical symmetrical pattern was observed in only nine out of the 16 normal subjects (56%). They described other atypical thermographic patterns, including those of DM patients, simply as "mottling and discrete areas of color variation."…”
Section: Use Of Thermography For Assessing Diabetic Foot: Unsolved Prmentioning
confidence: 89%
“…We are using infrared (IR) thermography Nishide et al, 2009), which were also used in some of the abovementioned studies of diabetic foot thermometry (Sun et al, 2005;Sun et al, 2008;Sun et al, 2006) and in the more recent report evaluating healing tendency of the diabetic foot ulcer (Bharara et al, 2010). Liquid crystal (LC) thermography was conventionally used in the papers published in 1980's and 90's (Benbow et al, 1994;Chan et al, 1991;Stess et al, 1986). Interestingly, LC thermography has been now reappraised by many recent researchers (Bharara et al, 2008a, b;Frykberg et al, 2009;Roback et al, 2009).…”
Section: Use Of Thermography For Assessing Diabetic Foot: Unsolved Prmentioning
confidence: 99%
See 1 more Smart Citation
“…In ischemic conditions, where blood perfusion may be [100] 2013 1b 1 ---Mori et al [101] 2013 3b 1 ---Najafi et al [102] 2012 2b 1 ---Barriga et al [103] 2012 2b 1 ---Balbinot et al [63] 2012 1b 2 -81.3 46.2 Nagase et al [61] 2011 1b 1 ---Bagavathiappan et al [104] 2010 2b 1 ---Kaabouch et al [105] 2009 3b ----Lavery et al [106] 2007 1a 1 ---Sun et al [107] 2006 2a 1 ---Armstrong et al [108] 2006 3b 1 ---Bharara et al [109] 2006 1b 1 ---Marcinkowska-Gapińska and Kowal [110] 2006 2a 1 ---Sun et al [111] 2005 2a 1 ---Armstrong et al [112] 2003 1b 1 ---Jiang et al [113] 2002 2a 1 ---Fujiwara et al [114] 2000 2a 1 ---Hosaki et al [115] 1999 2b ---Armstrong et al [116] 1997 1b 1 ---Benbow et al [62] 1994 1b 1 ---Stess et al [117] 1986 2a 1 ---Fushimi et al [118] 1985 3b 1 ---Sandrow et al [119] 1972 2-----Brånemark et al [120] 1967 1a ----reduced, especially at the periphery of the human body and limbs (hands and feet), these temperature pattern change [95]. Diabetic foot complications are expensive and they reduce the quality of life for many patients [96].…”
Section: Diabetesmentioning
confidence: 99%